Affordable and rapid HPTLC method for the simultaneous analysis of artemisinin and its metabolite artemisinic acid in Artemisia annua L. (31st March 2015) - Khan, Shazia; Ali, Athar; Ahmad, Shahzad; Abdin, Malik Zainul
Abstract Artemisinin (AN) and artemisinic acid (AA), valuable phyto‐pharmaceutical molecules, are well known anti‐malarials, but their activities against diseases like cancer, schistosomiasis, HIV, hepatitis‐B and leishmaniasis are also being reported. For the simultaneous estimation of AN and AA in the callus and leaf extracts of A. annua L. plants, we embarked upon a simple, rapid, selective, reliable and fairly economical high performance thin layer chromatography (HPTLC) method. Experimental conditions such as band size, chamber saturation time, migration of solvent front and slit width were critically studied and the optimum conditions were selected. The separations were achieved using toluene–ethyl acetate, 9:1 (v/v) as mobile phase on pre‐coated silica gel plates, G 60F254. Good resolution was achieved with Rf values of 0.35 ± 0.02 and 0.26 ± 0.02 at 536 nm for AN and 626 nm for AA, respectively, in absorption–reflectance mode. The method displayed a linear relationship with r2 value 0.992 and 0.994 for AN and AA, respectively, in the concentration range of 300–1500 ng for AN and 200–1000 ng for AA. The method was validated for specificity by obtaining in‐situ UV overlay spectra and sensitivity by estimating limit of detection (30 ng for AN and 15 ng for AA) and limit of quantitation (80 ng for AN and 45 ng for AA) values. The accuracy was checked by the recovery studies conducted at three different levels with the known concentrations and the average percentage recovery was 101.99% for AN and 103.84% for AA. The precision was analyzed by interday and intraday precision and was 1.09 and 1.00% RSD for AN and 1.22 and 6.05% RSD for AA. The analysis of statistical data substantiates that this HPTLC method can be used for the simultaneous estimation of AN and AA in biological samples. Copyright © 2015 John Wiley & Sons, Ltd.